Percepção dos agentes das cadeias produtivas da carne sobre os selos de qualidade em países ibero-americanos - Maysonnave, Greicy Sofia (2020)
There are many differentiating attributes that have been gaining space and prominence in the beef market, however one of the biggest challenges is to prove the veracity and importance of these attributes to consumers. Quality stamps represent one of the main ways of transmitting information in order to establish a relationship of trust with the final consumer. Therefore, the correct understanding of its importance as a guarantee of differentiation on the part of the production chain, as well as its recognition by the consumer are fundamental points for the success of the meat market. The general objective of this study was to analyze the perception of meat chains on quality stamps in Ibero-American countries. A quantitative online survey was conducted in different Ibero-American countries during the years 2017 and 2018. Two studies were generated using the data collected. Study 1 (n = 2077) addressed the perception of the quality of Ibero-American food products among Brazilian, Spanish and Portuguese consumers. Study 2 (n = 238) investigated the degree of knowledge about quality stamps of the different agents of the meat chain in Brazil and the harmony between them. Study 1 revealed that Brazilian consumers residing in Europe tend to behave similarly to the group of Portuguese and Spanish regarding shopping habits, as they expressed a high degree of harmony between the responses. The three groups of consumers (Portuguese and Spanish, Brazilian and Brazilian in Europe) showed similarity in relation to eating habits. The quality stamp has not added value to the product, in the opinion of most consumers. Portuguese and Spanish, Brazilians and Brazilians in Europe, expressed a neutral position regarding the valorization of fruits, vegetables, tubers, cocoa and confectionery / bakery with a quality stamp, as they indicated that the amount paid would be the same as normal products. The products of animal origin were valued in different ways according to the consumer group. Portuguese and Spanish would not buy food with a quality stamp, Brazilians would pay the same price as the normal ones. Valuation intention was observed in the group of Brazilians in Europe, as they were willing to pay 10 to 20% more for products with a quality stamp. With study 2, it can be seen that the perceptions of the agents of the meat production chain in Brazil indicate that there is a correct understanding of quality labels and their importance within the production system and a high degree of uniformity among the five different agents. These results point to a symmetrical information flow, which can be an important strategy both in seeking to meet consumer needs and in the correct dissemination of information about quality stamps. It is hoped that with the results obtained in the present study, strategies can be built for the development of quality stamps in the Ibero-American space, aiming at their valorization and recognition as a guarantee of quality.